Numerical evaluation of design factors for effective debris flow mitigation of closed-type check dams - Lee, Seungjun; An, Hyunuk; Kim, Minseok; Lee, Jinho (Frontiers in Earth Science, 2025)
Debris flows are one of the major natural disasters originating from mountainous areas, causing severe casualties and property damage when occurring near populated areas. Consequently, establishing structural and non-structural countermeasures against debris flows is essential in hazard-prone regions. This study aims to identify the critical factors for determining optimal locations of check dams, which are highly effective structures for mitigating debris flow damage. Numerical simulations were conducted using debris flow incidents from Raemian Apartments on 2011 Mt. Umyeon in Seoul and 2019 Gallam-ri in Gangwon-do, Republic of Korea. The simulation outcomes were quantitatively analyzed using Spearman’s rank correlation analysis. The results revealed that topographic features had a more significant impact on optimal check dam placement than flow characteristics. Specifically, check dams located at sites capable of storing large volumes of debris were the most effective in reducing debris flow damage.